Model Kuantitatif Keselamatan Pelayaran: Dominasi Faktor Manusia di Pelabuhan Tanjung Emas - Simpliano Darmentos Dedo (Indonesian Maritime Researchers and Lecturers, 2025)
Sea transportation plays a crucial role in supporting national development, particularly in transporting goods and passengers. Tanjung Emas Port in Semarang, as a major port with high traffic, faces significant challenges in ensuring navigational safety. This study aims to analyze the partial effects of three key operational factors—Communication System (X1), Safety Facilities (X2), and Crew Competence (X3)—on Navigational Safety (Y). A quantitative approach was used with a sample of 100 ship crew members, selected using incidental sampling. Data were analyzed through descriptive statistics and Multiple Linear Regression (MLR) using SPSS. The results indicate that all three independent variables have a positive and significant effect on navigational safety. The regression equation obtained, Y = -1.398 + 0.218X1 + 0.278X2 + 0.302X3 + μ, shows that Crew Competence (X3) is the most dominant variable in predicting navigational safety outcomes. Collectively, these variables explain 72.4% of the variance in navigational safety. These findings emphasize that human competence and adherence to procedural discipline are critical leverage points in improving safety performance at ports.